Messy, Butch, and Queer: LGBTQ Youth and the School-to-Prison Pipeline. (January 2015) - Snapp, Shannon D.; Hoenig, Jennifer M.; Fields, Amanda; Russell, Stephen T.
Emerging evidence suggests that lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) youth experience disparate treatment in schools that may result in criminal sanctions. In an effort to understand the pathways that push youth out of schools, we conducted focus groups with youth ( n = 31) from Arizona, California, and Georgia, and we interviewed adult advocates from across the United States ( n = 19). Independent coders used MAXQDA to organize and code data. We found that LGBTQ youth are punished for public displays of affection and violating gender norms. Youth often experience a hostile school climate, may fight to protect themselves, and are frequently blamed for their own victimization. Family rejection and homelessness facilitate entry in the school-to-prison pipeline. Narratives highlight new opportunities to challenge inequity in schools.